Hubungan Lama Penggunaan Ventilator Mekanik dengan Mortalitas di Intensive Care Unit (ICU) RSUD Karawang - Kusnanto, Kusnanto; Burhanudin, Akim (Universitas Malahayati, 2025)
ABSTRACT Patients on mechanical ventilators are usually critically ill patients with multiorgan failure. Continued infection for more than 48 hours can cause the patient's prognosis to worsen and increase mortality. Karawang Regional Hospital in the ICU in 2022 found 49.7% of patients who died with mechanical ventilators for > 48 hours, likewise in 2023 it was found that 65.8% of patients died with mechanical ventilators for > 48 hours. To determine the relationship between the length of use of a mechanical ventilator and mortality in the ICU of Karawang Regional Hospital in 2024.Retrospective cohort quantitative analytical study with a cross sectional design. The research sample of patients using mechanical ventilators in the ICU consisted of 84 respondents using a simple random sampling technique. Secondary data using a checklist sheet was analyzed using the chi square test. The results of univariate analysis showed that the majority of mechanical ventilator use was ≥ 48 hours, 65.5% and 77.4% experienced death. The results of bivariate analysis showed a relationship between the length of use of a mechanical ventilator and mortality with p value = 0.000. The length of use of a mechanical ventilator is related to mortality. It is hoped that health workers, especially in the ICU, will carry out routine respiratory tract care, including maintaining oral hygiene with an antiseptic, holding regular training for ICU staff regarding the importance of preventing VAP and early detection of infection, as well as carrying out regular monitoring of mechanical ventilator users and evaluating the effectiveness of protocols for continuous improvement. Keywords: Duration of Mechanical Ventilator Use, ICU. ABSTRAK Pasien dengan ventilator mekanik biasanya adalah pasien dengan sakit kritis (critically ill) dengan kegagalan multiorgan. Infeksi lanjutan lebih dari 48 jam dapat menyebabkan prognosis pasien memburuk dan meningkatkan mortalitas. RSUD Karawang di ruang ICU pada tahun 2022 pasien yang meninggal ditemukan 49,7% dengan pemasangan ventilator mekanik > 48 jam, begitu juga pada tahun 2023 ditemukan 65,8% dengan pemasangan ventilator mekanik > 48 jam. Mengetahui hubungan lama penggunaan ventilator mekanik dengan mortalitas di ICU RSUD Karawang tahun 2024. Penelitian analitik kuantitatif kohort retrospektif dengan rancangan cross sectional. Sampel penelitian pasien yang menggunakan ventilator mekanik di ICU berjumlah 84 responden dengan teknik simple random sampling. Data sekunder menggunakan lembar cheklist dianalisis menggunakan uji uji chi square. Hasil analisis univariat diketahui sebagian besar lama penggunaan ventilator mekanik ≥ 48 jam sebanyak 65,5% dan mengalami kematian sebanyak 77,4%. Hasil analisis bivariat ada hubungan antara lama penggunaan ventilator mekanik dengan mortalitas dengan p value = 0,000. Lama penggunaan ventilator mekanik berhubungan dengan mortalitas. Diharapkan tenaga kesehatan khususnya di ruang ICU melakukan perawatan saluran pernapasan secara rutin termasuk menjaga kebersihan mulut dengan antiseptic, mengadakan pelatihan berkala bagi staf ICU mengenai pentingnya pencegahan VAP dan deteksi dini infeksi serta melakukan monitor secara berkala pada pengguna ventilator mekanik dan evaluasi efektivitas protokol untuk perbaikan berkelanjutan. Kata Kunci: Lama Penggunaan Ventilator Mekanik, ICU